The Development of Word Card Media to Improve Beginning Reading Proficiency among Grade 2 Students at SDN 07 Koto Baru - Martiya Nurni Khairita; Sri Yunimar Ningsih; Pretty Pahnia Julita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the fact that many second-grade elementary school students are still unable to read. The researcher’s effort to address this issue was to develop a learning medium in the form of word cards, aimed at increasing students’ interest in reading, particularly in the Indonesian language subject, on the topic of types of occupations, using attractive images. This study employs a research and development (R&D) methodology. The development model used is the Four-D (4D) model, which includes: Define, Design, Development, and Dissemination. In the Define stage, needs analysis, material analysis, learner characteristics analysis, and curriculum analysis were conducted. In the Design stage, instructional module and word card media designs were developed. In the Development stage, validation tests, practicality tests, and effectiveness tests were carried out. In the Dissemination stage, the developed Indonesian language word card media was distributed, limited to SDN 07 Koto Baru. The research and development process resulted in a word card learning medium for second-grade students at SDN 07 Koto Baru. The media was validated by three validators, and the average validation score of the word card media reached 89%, categorized as very valid. In terms of practicality, responses from teachers and students showed an average score of 93.82%, categorized as very practical. The effectiveness test, conducted with 21 students who used the developed word card media during learning, showed an average score of 77.99%, indicating the media is effective. It can thus be concluded that the word card media is engaging, suitable for use in the learning process, and has potential for further development.